(untitled) (KYAMC Journal, 2017)
The article reviews the relationship between type 2 diabetes and obesity. This also includes types of obesity and it’s genetic predisposition. The modern generalization of sedentary life style and caloric abundance has created new physiological conditions capable of changing the level of expression of a number of genes involved in fuel metabolism and body weight regulation. In this article, we underscore the importance of obesity in relation to disorders of diverse etiologies characterized by disturbances of free fatty acids, visceral adiposity and insulin resistance. Further, we have investigated the role of selecting the traits to be subjected to quantitative genetic analysis in the occurrence of obesity. KYAMC Journal Vol. 4, No.-1, July 2013, Page 357-361